2008
DOI: 10.1097/chi.0b013e31816bffb7
|View full text |Cite
|
Sign up to set email alerts
|

A Replication of the Autism Diagnostic Observation Schedule (ADOS) Revised Algorithms

Abstract: Objective-To replicate the factor structure and predictive validity of revised Autism Diagnostic Observation Schedule algorithms in an independent dataset (N = 1,282).Method-Algorithm revisions were replicated using data from children ages 18 months to 16 years collected at 11 North American sites participating in the Collaborative Programs for Excellence in Autism and the Studies to Advance Autism Research and Treatment.Results-Sensitivities and specificities approximated or exceeded those of the old algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
193
7
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(214 citation statements)
references
References 13 publications
13
193
7
1
Order By: Relevance
“…Hence, our findings might not fully generalize to children and adolescents with more severe forms of ASD. Earlier studies have already shown a relatively poor sensitivity of the ADOS (ranging from .49 to .80) in classifying individuals with PDD-NOS (Bastiaansen et al 2010;Gotham et al 2008). However, it should also be noted that in the current study the distribution of clinical diagnoses (autism, syndrome of Asperger, PDD-NOS) was not significantly different for participants scoring above or below the ADOS cutoff for an ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, our findings might not fully generalize to children and adolescents with more severe forms of ASD. Earlier studies have already shown a relatively poor sensitivity of the ADOS (ranging from .49 to .80) in classifying individuals with PDD-NOS (Bastiaansen et al 2010;Gotham et al 2008). However, it should also be noted that in the current study the distribution of clinical diagnoses (autism, syndrome of Asperger, PDD-NOS) was not significantly different for participants scoring above or below the ADOS cutoff for an ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive diagnostic procedures, only thirtyseven percent of the participants (n = 57) received a total score on the ADOS at or above the cutoff point for ASD (C7). Earlier studies have already shown a relatively poor sensitivity of the ADOS (ranging from .49 to .80) in classifying individuals with PDD-NOS (Bastiaansen et al 2010;Gotham et al 2008). Therefore, all statistical analyses were repeated to check whether results differed between individuals scoring below or at/above the ADOS cutoff point.…”
Section: Participantsmentioning
confidence: 99%
“…To confirm, however, whether a child indeed met diagnostic classification criteria for the ASD group, each child was further evaluated. The decision to classify a child in the ASD group was based on: (i) results on the revised algorithm of the ADOS (Lord et al, 2000; Gotham, Risi, Dawson, Tager-Flusberg, Joseph, Carter, et al, 2008), administered and scored by trained, certified clinicians; (ii) results on The Social Communication Questionnaire (SCQ; Berument, Rutter, Lord, Pickles, & Bailey,1999), a parent-report measure; and (iii) results of a consensus clinical diagnosis made by a multidisciplinary team in accord with DSM-IV criteria (American Psychiatric Association, 2002). In all cases, a diagnosis of ASD was supported by ADOS scores at or above cutoffs for PDD-NOS and by the consensus clinical diagnosis.…”
Section: Participantsmentioning
confidence: 99%
“…Using a clinical best estimate diagnostic approach following criteria in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, 25 and following a method used in previous published research studies that includes clinical judgment, 23,26,27 each case was classified as ASD or non-ASD.…”
Section: Methodsmentioning
confidence: 99%